Curcumin: Phytochemical Therapy for Treating Hyperlipidemia - Pehlivanović, B.; Bečić, F. (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2018)
In modern world, hyperlipidemia is the most common disorder mainly caused by lifestyle habits and the major cause of cardiovascular, coronary and atherosclerotic changes. Such disorder is characterized by abnormally elevated levels of any or all lipids or lipoproteins in the blood. A wide range of drugs are available for the treatment of hyperlipidemia, class of antihyperlipidemic drugs, but such drug-therapies are carried out with presence of various side effects. In the last decades, different in vitro and in vivo research have been conducted to confirm the therapeutic effects of various phytochemical agents that overcome the side effects caused by synthetic drugs. According to Ayurvedic recommendations and experimental studies, numerous phytochemical agents have been reported to possess different antihyperlipidemic properties. One of the most studied phytochemical agent - curcumin, herbal polyphenol and active ingredient which can be extracted from the powder rhizome of the plant Curcuma longa, has been reported to possess a wide range of pharmacological properties such as antimicrobial, antioxidative, antiinflammatory and anticancer property. Recent studies also suggests curcumin as potential lipid lowering candidate in treatment of hyperlipidemia. The aim of this review is to present and discuss phytochemistry, molecular mechanism of hypolipidemic activity of curcumin, demonstrating its importance as potential therapy for the treatment of hyperlipidemia.